Interstitial duplication of 22q13.2 in a girl with short stature, impaired speech and language, and dysmorphism - Samanich, Joy; Montagna, Cristina; Morrow, Bernice E.; Babcock, Melanie (Journal of Pediatric Genetics, 2012)
The 22q13.3 deletion syndrome has been widely reported, with a known phenotype including global developmental delay, normal to accelerated growth and a characteristic facial appearance. A duplication syndrome involving this region has also been reported, with a somewhat more variable phenotype including psychomotor retardation, growth restriction, characteristic facial appearance differing from that seen in the deletion syndrome, and multiple malformations. The majority of reported patients have terminal duplications, with only three previous reports of interstitial duplication of the region. Herein we report a young woman with a de novo 569 kb interstitial duplication of 22q13.2 and short stature, speech and language impairment, refractive amblyopia, menorrhagia and facial dysmorphism. Comparison of her phenotype to previously reported patients with interstitial duplications reveals common traits including growth restriction, craniofacial anomalies and developmental delays. Included in the duplicated region is the gene EP300, mutations and deletions of which are implicated in Rubinstein-Taybi syndrome and thyrotroph embryonic factor, which has been proposed to be related to the pituitary hypoplasia seen in one patient with a large duplication, and several other genes without clear relation to disease.
Keywords: Copy number variation; microduplication; speech and language impairment; array comparative genomic hybridization